Bone turnover markers in women can predict low bone mineral density - Agrawal, B. K.; Jain, Vaishali; Varshney, Atul (International Journal of Research in Medical Sciences, 2017)
Background: Morbidity and mortality associated with osteoporosis continues to be high in India due to late diagnosis. This study aims to find the difference in the levels of bone turn over markers in premenopausal and postmenopausal women, in order to assess whether these markers can be used as predictors of low bone mineral density which can develop in later life. Methods: Study was conducted on 350 women aged 30-65 years. Women were classified into premenopausal and postmenopausal groups based on their menstrual history. Serum samples were analyzed for osteocalcin and telopeptide-C. Student’s t-test and logistic regression are used for statistical confirmations. Results: Levels of these markers (ng/ml) were found to be lower in premenopausal women (Osteocalcin = 9.0 ± 1.0; telopeptide-C = 0.270 ± 0.099) than in postmenopausal women (Osteocalcin = 9.8 ± 1.7; telopeptide-C = 0.490 ± 0.135) and this difference was found to be significant (P <0.001) for both the markers. In both the groups, telopeptide-C made significant contribution to prediction of low BMD [(Premenopausal group - odds ratio (OR) = 2.9; 95% confidence interval (95%CI) = 1.3-6.5 and postmenopausal group - OR = 9.6; 95%CI = 6.0-13.23) but osteocalcin could not (premenopausal group - OR = 0.91; 95%CI = 0.58-1.42 and postmenopausal group - OR = 0.87; 95%CI = 0.54-1.4)]. In premenopausal women increase in telopeptide-C by a unit increased chance of developing low BMD by 2.9 times while in postmenopausal women increase in telopeptide-C by a unit increased chance of developing low BMD by 9.6 times. Conclusion: Women with higher levels of telopeptide-C need to be identified at an early stage as it provides with an early warning of the possibility of future development of osteoporosis so that preventive measures can be taken timely.